2018
DOI: 10.1088/1742-5468/aab856
|View full text |Cite
|
Sign up to set email alerts
|

Computing return times or return periods with rare event algorithms

Abstract: The average time between two occurrences of the same event, referred to as its return time (or return period), is a useful statistical concept for practical applications. For instance insurances or public agency may be interested by the return time of a 10 m flood of the Seine river in Paris. However, due to their scarcity, reliably estimating return times for rare events is very difficult using either observational data or direct numerical simulations. For rare events, an estimator for return times can be bui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 93 publications
1
74
0
Order By: Relevance
“…If on the contrary the resampling time is much larger than the autocorrelation time, the trajectories will fall back to the typical states, and the importance sampling efficiency will be lost. Tests with simpler systems [22] have shown that the precise value of τ does not affect the results, as long as it is of the order of the autocorrelation time. The trajectories are perturbed after cloning by adding a small random field to the surface pressure, as described in [26].…”
Section: Analysis Of Large Deviations Of Europe Surface Temperature Imentioning
confidence: 99%
See 2 more Smart Citations
“…If on the contrary the resampling time is much larger than the autocorrelation time, the trajectories will fall back to the typical states, and the importance sampling efficiency will be lost. Tests with simpler systems [22] have shown that the precise value of τ does not affect the results, as long as it is of the order of the autocorrelation time. The trajectories are perturbed after cloning by adding a small random field to the surface pressure, as described in [26].…”
Section: Analysis Of Large Deviations Of Europe Surface Temperature Imentioning
confidence: 99%
“…Thanks to the rare event algorithm, we can extend the estimate of the return time curve to much rarer events. The return time can be computed from the output of the rare event algorithm as described in details in [26] and [22]. The red line in figure 7b) has been obtained by computing return time functions from the experiments with the algorithm (the case k * = 20 and k * = 40 repeated twice with different sets of initial conditions to improve the statistics) and averaging the results in the areas of overlap.…”
Section: Using the Large Deviation Algorithm For Extreme Heat Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because AMS is used with a deterministic final time, it is worth noted that the best importance function should depend on time (see [37] section IIIC, see also [7]). Also note that using all these trajectories with intermediate levels , it is easy to generate an approximation of the curve → r( ).…”
Section: On the Importance Functionmentioning
confidence: 99%
“…A committor function is the probability that an event will occur or not in the future, as a function of the current state of the system. For the El-Niño case, this committor function will be the probability that an observable O of the system reaches a given threshold within a time T [18]. The definition and mathematical properties of committor functions are introduced in section III.…”
Section: Introductionmentioning
confidence: 99%